Strengthening firm sustenance through entrepreneurial innovation: Evidence from the Nigerian industrial goods sector - Gilbert Ogechukwu Nworie; Christopher Chinedu Onochie; Nkiru Peace Nwakoby (Annals of Management and Organization Research, 2025)
Purpose: The dearth of innovation not only limits operational efficiency, but also exposes firms to heightened risks of obsolescence and market displacement. Thus, this study ascertains the effect of entrepreneurial innovation on the sustainability of listed industrial goods firms in Nigeria. Research Methodology: A sample size of eight out of 13 listed industrial goods firms was selected. Using the ex-post facto research strategy, secondary data were extracted from firms’ annual reports over a ten-year period (2014-2023). Analyses were performed using descriptive test, linearity test, heteroskedasticity test, autocorrelation test, and ordinary least square regression. Results: It was found that entrepreneurial innovation practice significantly enhances firm sustenance (proxy by operating cash flow ratio) among listed Nigerian industrial goods firms (b = 0.352574; p-value = 0.004759). Conclusions: By fostering a culture of innovation, investing in research and development, and leveraging modern technologies, firms can position themselves for long-term success despite prevailing economic challenges. Limitations: One limitation of this study is the small sample size, as only eight of the 13 listed industrial goods firms in Nigeria were included. Contribution:  This study contributes to the literature by addressing the gap in the existing literature on entrepreneurial innovation in industrial goods firms, particularly publicly listed firms in Nigeria, an area largely overlooked in prior research on SMEs and niche industries. Recommendation: This study recommends that company executives establish dedicated innovation departments or strengthen existing ones to drive continuous improvement in the firm.